"I now look forward to the future, by finding things from our past…"Exploring the potential of metal detector archaeology as a source of well-being and happiness for British Armed Forces veterans with mental health impairments: 50-year-old male war veteran and survey participant, suffering from PTSD and depression, on the effect of metal detecting. Issue 4 (2nd April 2020) - Dobat, Andres S.; Wood, Sultan Oruc; Jensen, Bo Søndergaard; Schmidt, Sören; Dobat, Armin S.
ABSTRACT: This article presents the results of a questionnaire-based survey of the perceived effects of metal detecting among British Armed Forces veterans with PTSD (Post Traumatic Stress Disorder) and/or other diagnosed or undiagnosed psychological disorders. Although the qualitative analysis presented here is only a first step towards understanding its beneficial effects, the authors conclude that archaeological metal detecting can be regarded as having the potential to positively influence well-being and happiness for people suffering from mental health problems. The findings suggest that practitioners feel that metal detecting has a significantly positive and lasting effect on their health and well-being. A significant number of respondents feel that metal detecting has alleviated specific symptoms of their mental disorders (PTSD, depression, anxiety disorders). The key factors for the beneficial effect of metal detecting appear to be of a mental, sensory, physical and social nature. First and foremost, however, its beneficial effect seems to be deeply rooted in the fact that the participants interact with archaeological heritage.